Analisis Masalah Kesehatan Pada Program Tuberkulosis di Dinas Kesehatan Kota Kediri Tahun 2024 - Ramadhani, Nabhilah Suci; Wahyuni, Chatarina Umbul; Rahayu, Tiwuk Puji; Syam, Sadli (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Tuberculosis remains a significant global public health challenge. Indonesia ranks second in the world for TB prevalence. In Kediri City, while CDR-TB and CNR-TB meet targets, TB enrollment remains inadequate, highlighting obstacles in accessing health services. This study aims to determine priorities, identify causes, and propose alternative solutions for the TB program. Additionally, it describes TB enrollment trends from 2021-2023 and January-June 2024 in Kediri City.Methods: This descriptive observational study was conducted at the Kediri City Health Office from July 8-August 2, 2024, involving 28 informants. Data were obtained through in-depth interviews and document analysis. Priorities were determined with the USG method, causes were analyzed using the web of causation, and alternative solutions were developed using the CARL method.Results: The results of the analysis show that TB enrollment rates in Kediri City have significantly decreased each year, with rates of 82.9% in 2021, 79.8% in 2022, and 72.6% in 2023. In 2024, the highest rate was 75.5% in February, and the lowest was 57.9% in April. Factors contributing to this decline include suboptimal coordination between health facilities, limited human resources, high public stigma towards TB, and patient absenteeism.Conclusions: The low TB enrollment rate in Kediri City is a priority issue. Recommendations include routine SITB monitoring, educational efforts to reduce TB stigma, improved coordination with private practitioners via WhatsApp groups, regular meetings, home visits, and increasing the number of competent staff for counseling, case finding, and patient support.